ANALISIS EFEKTIVITAS BIAYA PASIEN COVID-19 MENGGUNAKAN TERAPI OKSIGEN DAN REMDESIVIR DI RSUD KABUPATEN TANGERANG - Yusransyah, Yusransyah; Udin, Baha; Abdillah , Mursyid; Murdianto, Yudi; Soraya Uli, Elisabeth; Suryana, Nana (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
COVID-19 is a contagious disease, so there is a potential for an increase in the number of COVID-19 cases. If there is an increase in incidence or prevalence, it will cause problems related to the costs and outcomes of an intervention. Therefore, a cost-effectiveness analysis is needed. This study aims to determine the cost-effectiveness of COVID-19 patients who use oxygen therapy with and without being given remdesivir. This study uses a cost-effectiveness analysis method that takes into account the ACER (Average Cost-Effectiveness Ratio) and ICER (Incremental Cost-Effectiveness Ratio) values. The data used is retrospective data and sampling is done by purposive sampling, the sample obtained in this study amounted to 34 cases. The results of this study showed that the total average direct medical costs of the remdesivir group were Rp. 32,399,532 with an effectiveness of 47%, while in the non-remdesivir group the total average direct medical costs were Rp. 26,853,729 with an effectiveness of 41%. The ACER value obtained in this study was Rp. 688,490 in the remdesivir group and Rp. 654,969 in the non-remdesivir group. The results of the ICER calculation in this study were Rp. 924,301 per day of hospitalization. In this study, it can be concluded that the therapy group of COVID-19 patients who use oxygen therapy without being given remdesivir is more cost-effective than the therapy group of COVID-19 patients who use oxygen therapy with remdesivir.